Integrating Circular Economy and Islamic Values in Indonesia’s Fashion Industry - Hayati, Nur; Isa, Muzakar; Fuadah, Rowiyatul (Value Added : Majalah Ekonomi dan Bisnis, 2026)
Indonesia’s fashion industry remains largely shaped by a linear economic model that privileges mass production and rapid consumption, thereby exacerbating textile waste and intensifying environmental pressures. Although a transition towards a circular economy has become increasingly urgent, this shift is constrained by high implementation costs, systemic complexity, technological limitations, and a persistent gap between consumer awareness and actual purchasing behaviour. This study develops an integrative conceptual framework that brings together Circular Economy (CE), Lean Production (LP), Industry 4.0 (I4.0), and Islamic values through a descriptive qualitative approach grounded in an extensive literature review and critical analysis. The findings indicate that lean production, when implemented without alignment to circular principles, may inadvertently reinforce linear fast fashion practices. By contrast, reconceptualising lean production as sustainable lean production, supported by I4.0 technologies, can reduce the costs associated with reverse logistics while effectively managing the complexity inherent in circular systems. Islamic values function as an ethical foundation that strengthens commitments to sustainability, transparency, and responsible consumption behaviour. Overall, the proposed framework offers a coherent pathway for simultaneously reconciling economic efficiency with environmental responsibility.